HUBUNGAN POSISI IBU BERSALIN PADA KALA I FASE AKTIF DENGAN KEMAJUAN PERSALINAN DI RS AWAL BROS PANAM PEKANBARU TAHUN 2023 - Sriwahyuni, Eka; Siregar, G.F Gustina; Afriza, Afriza (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2024)
The progression of labor is influenced by three main factors: power, the birth canal, and the fetus. Additionally, studies indicate that the mother's position can enhance the labor process (Bonny, D. 2018). Labor begins with the onset of regular contractions, the expulsion of bloody mucus (known as the bloody show), and cervical dilation, marking the first stage of labor. This stage concludes when the cervix is fully dilated; it typically lasts around 13 hours for first-time mothers (with a latent phase of 7-8 hours and an active phase of 5-6 hours) and about 7 hours for those who have given birth before (with a latent phase of 4 hours and an active phase of 3 hours) (Hanifa, W. 2018).The study aimed to investigate the relationship between maternal positioning during the active phase of labor and the progression of labor at Awal Bros Panam Hospital in Pekanbaru. The study involved maternity patients in the active phase at the hospital, with a sample size of 30 participants selected through total sampling. Data collection utilized a partograph checklist. Univariate analysis revealed that 20% of respondents were under 20 or over 35 years old, while 80% were aged 20-35. Among the participants, 30% were first-time mothers (primigravidas) and 70% were experienced mothers (multigravidas). Out of the 30 respondents who adopted walking, squatting, or tilted positions, 17 (56.7%) experienced progress in labor, while 13 (43.3%) did not. Statistical analysis using the Chi-Square test yielded a p-value of 0.001, indicating a significant relationship between maternal position during the active phase of labor and labor progression at Awal Bros Panam Hospital, Pekanbaru. The results suggest that maternal positioning plays a crucial role in labor progression. This research may serve as a valuable resource for enhancing midwifery services by providing information and counseling to mothers about effective positions before delivery.